HYPER-PERSONALIZATION IN MARKETING: REDEFINING CONSUMER EXPECTATIONS IN THE AGE OF BIG DATA - Bilgah Bilgah; Suripah Suripah; Murniyati Murniyati; Eka Putri Handayani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research examines the impact of hyper-personalization and big data usage on consumer expectations and customer engagement within the context of the Spotify platform. Utilizing a quantitative research design, data were collected from 150 students at the Faculty of Economics and Business, Bina Sarana Informatika University, through a structured questionnaire. The analysis employed Smart PLS to evaluate the relationships between the variables, with consumer expectations as the dependent variable, hyper-personalization and big data usage as independent variables, and customer engagement as an intervening variable. The findings reveal that while big data usage significantly enhances customer engagement, its direct influence on consumer expectations is negligible. Conversely, hyper-personalization demonstrates a strong positive effect on both consumer expectations and customer engagement. Furthermore, customer engagement positively impacts consumer expectations, indicating that increased interaction with personalized content elevates user satisfaction. These results suggest that marketers should focus on implementing effective hyper-personalization strategies to optimize consumer experiences and foster brand loyalty in the competitive digital music streaming landscape. This study contributes valuable insights into consumer behavior, emphasizing the essential role of data-driven personalization in shaping user expectations and engagement.